AURELIA Analysis Shows Benefits of Bevacizumab as Add-on Therapy in Ovarian Cancer - Vinall, Phil (MD Conference Express, 2012)
In patients with ovarian cancer, progression-free survival and overall response rate are significantly improved with the addition of bevacizumab to chemotherapy in front-line [Burger RA et al. N Engl J Med 2011] and platinum-sensitive recurrent [Aghajanian C et al. J Clin Oncol 2012] settings, and as shown in the Phase 3 AURELIA: A Study of Avastin (Bevacizumab) Added to Chemotherapy in Patients with Platinum-Resistant Ovarian Cancer [AURELIA; NCT00976911] trial [Pujade-Lauraine E et al. J Clin Oncol 2012].